Comparison of Discectomy versus Sequestrectomy in Lumbar Disc Herniation: A Retrospective Cohort Study: Assessment of Lumbar Disc Herniation - Mehmood, Asad Ullah; Shakeel, Muhammad; Talha, Muhammad; Qasmi, Shahzad Ahmad; Afzal, Waseem; Inam, Shahzad (Pakistan Journal of Health Sciences, 2024)
Lumbar disc herniation is a common spinal condition characterized by the protrusion or extrusion of intervertebral disc material. This extruded or protruded disc material compresses the spinal nerves causing various symptoms such as low back pain radiculopathy and functional limitation. Objective: To assess and compare the outcomes of pain relief as well as functional improvement among patients who underwent Discectomy and Sequestrectomy. Methods: A retrospective cohort study was conducted at the neck and surgery department, Combined Military Hospital (CMH), Quetta. A total of 80 patients were included in the study, 26 (32.5%) patients underwent Sequestrectomy while microdiscectomy was done in 54 (67.5%) patients. The data collection proforma consisted of demographic information, baseline clinical characteristics, description of surgical procedures, pre and postoperative VAS scores, and functional outcomes assessed by the Oswestry disability index. The statistics used in this study were independent t-test and paired t-tests. Results: The study results showed no significant differences in the baseline characteristics between the groups. Both procedures showed a significant improvement in pain levels, in terms of lowered VAS scores and ODI scores. Conclusions: The procedure of sequestrectomy has shown significant improvements in postoperative pain relief and functional outcomes as compared to microdiscectomy.